Pengaruh Tingkat Pendidikan, Status dan Pendapatan terhadap Penerapan Akuntansi Rumah Tangga - Ginting, Wenny Anggeresia; Siregar, Melinda; Nasution, Siti Aisyah; Maryadi, Dominikus Andreo (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the influence of education level, status and income on the implementation of household accounting. The population in this study were lecturers, administrative officers and students of the Menado State Polytechnic. The sampling technique used in this research was purposive sampling. The research results show that simultaneously there is an insignificant influence between education level, status and income on the implementation of household accounting. Only the status variable has a significant influence on the implementation of secondary accounting among lecturers, administrative officers and students at the Menado State Polytechnic.